Retinal ganglion cell loss in neuromyelitis optica: a longitudinal study - Oertel, Frederike C.; Havla, Joachim; Roca-Fernández, Adriana; Lizak, Nathaniel; Zimmermann, Hanna; Motamedi, Seyedamirhosein; Borisow, Nadja; White, Owen B.; Bellmann-Strobl, Judith; Albrecht, Philipp; Ruprecht, Klemens; Jarius, Sven; et al. (Journal of neurology, neurosurgery, and psychiatry, 2018)
Objectives Neuromyelitis optica spectrum disorders (NMOSD) are inflammatory conditions of the central nervous system and an important differential diagnosis of multiple sclerosis (MS). Unlike MS, the course is usually relapsing, and it is unclear, if progressive neurodegeneration contributes to disability. Therefore, we aimed to investigate if progressive retinal neuroaxonal damage occurs in aquaporin4-antibody-seropositive NMOSD. - Methods Out of 157 patients with NMOSD screened, 94 eyes of 51 patients without optic neuritis (ON) during follow-up (F/U) and 56 eyes of 28 age-matched and sex-matched healthy controls (HC) were included (median F/U 2.3 years). The NMOSD cohort included 60 eyes without (EyeON −) and 34 eyes with a history of ON prior to enrolment (EyeON+). Peripapillary retinal nerve fibre layer thickness (pRNFL), fovea thickness (FT), volumes of the combined ganglion cell and inner plexiform layer (GCIP) and the inner nuclear layer (INL) and total macular volume (TMV) were acquired by optical coherence tomography (OCT). - Results At baseline, GCIP, FT and TMV were reduced in EyeON+ (GCIP p<2e−16; FT p=3.7e−4; TMV p=3.7e−12) and in EyeON − (GCIP p=0.002; FT p=0.040; TMV p=6.1e−6) compared with HC. Longitudinally, we observed GCIP thinning in EyeON− (p=0.044) but not in EyeON+. Seven patients had attacks during F/U; they presented pRNFL thickening compared with patients without attacks (p=0.003). - Conclusion This study clearly shows GCIP loss independent of ON attacks in aquaporin4-antibody-seropositive NMOSD. Potential explanations for progressive GCIP thinning include primary retinopathy, drug-induced neurodegeneration and retrograde neuroaxonal degeneration from lesions or optic neuropathy. pRNFL thickening in the patients presenting with attacks during F/U might be indicative of pRNFL susceptibility to inflammation.